Design, Formulation, and Evaluation of Andrographolide-Loaded Mucoadhesive Microspheres for Targeted Delivery in Helicobacter pylori-Associated Peptic Ulcer Therapy (International Journal of Environmental Sciences, 2025)
The present investigation focused on the formulation and evaluation of andrographolide-loaded mucoadhesive microspheres, developed to provide localized drug delivery to the gastric mucosa for the effective treatment of Helicobacter pylori-associated peptic ulcers. Two formulation techniques—ionic gelation (chemical stabilization) and emulsion-solvent evaporation (heat stabilization)—were employed using chitosan as the primary mucoadhesive polymer. The prepared microspheres were systematically characterized for their particle size, surface morphology, drug entrapment efficiency, swelling index, mucoadhesive strength, and in vitro drug release profile. All microspheres exhibited a spherical morphology with particle sizes ranging from 48.6 µm to 58.7 µm. Drug entrapment efficiency was observed in the range of 63.5% to 80.3%, and the release of andrographolide extended up to 12 hours, indicating sustained release characteristics. Notably, an increase in polymer concentration led to a significant enhancement in both the swelling index and mucoadhesive strength, highlighting the potential for prolonged gastric retention. Among the tested formulations, F6—prepared using the heat stabilization method and a higher concentration of chitosan—emerged as the most promising, demonstrating the highest entrapment efficiency, sustained drug release (91.5% at 12 hours), and superior mucoadhesive properties. These findings underscore the potential of andrographolide-loaded chitosan microspheres as an effective localized therapy for peptic ulcers, offering controlled drug release while reducing systemic exposure and side effects.